2009
DOI: 10.1089/vbz.2008.0147
|View full text |Cite
|
Sign up to set email alerts
|

Low West Nile Virus Circulation in Wild Birds in an Area of Recurring Outbreaks in Southern France

Abstract: West Nile virus (WNV) has a history of irregular but recurrent epizootics in countries of Mediterranean and of Central and Eastern Europe. We have investigated the temporal enzootic activity of WNV in free-ranging birds over a 3-year period in an area with sporadic occurrences of WNV outbreaks in Southern France. We conducted an intensive serologic survey on several wild bird populations (>4000 serum samples collected from 3300 birds) selected as potential indicators of the WNV circulation. WNV antibodies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…This is in accordance with findings from other studies carried out in the last few years, in which no or limited WNV circulation was reported in Spain [3.8% (Ló pez et al 2008) and 2.2% (Ló pez et al 2010)] and other Mediterranean and European countries: Morocco [3.5% (Figuerola et al 2009)], Germany [1.6% (Linke et al 2007)], France [0.0-4.8% (Lena et al 2006, Jourdain et al 2007, Balança et al 2009)], Poland [5.2% (Hubálek et al 2008a)], or the Czech Republic [5.9% (Hubálek et al 2008b)]. However, higher seroprevalences have been also reported in Spain [7.8-10.4 (Figuerola et al 2007a], France [8.0% (Hars et al 2004)], the United Kingdom [14.7% (Buckley et al 2003)], and Italy [49.1% (Monaco et al 2009)].…”
supporting
confidence: 92%
“…This is in accordance with findings from other studies carried out in the last few years, in which no or limited WNV circulation was reported in Spain [3.8% (Ló pez et al 2008) and 2.2% (Ló pez et al 2010)] and other Mediterranean and European countries: Morocco [3.5% (Figuerola et al 2009)], Germany [1.6% (Linke et al 2007)], France [0.0-4.8% (Lena et al 2006, Jourdain et al 2007, Balança et al 2009)], Poland [5.2% (Hubálek et al 2008a)], or the Czech Republic [5.9% (Hubálek et al 2008b)]. However, higher seroprevalences have been also reported in Spain [7.8-10.4 (Figuerola et al 2007a], France [8.0% (Hars et al 2004)], the United Kingdom [14.7% (Buckley et al 2003)], and Italy [49.1% (Monaco et al 2009)].…”
supporting
confidence: 92%
“…and a type of West Nile Virus (a Flavivirus) were also detected in ticks, but could not be confirmed. Both agents are known to be transmitted by different species of soft ticks (Lawrie et al., 2004, Cutler, 2010) and WNV has been previously reported in the Camargue region (Balança et al., 2009, Vittecoq et al., 2013, Pradier et al., 2014). However, a previous study of Yellow-legged gulls on Carteau did not find evidence for the presence of Flavivirus antibodies in eggs, suggesting that WNV and other related viruses may not have circulated in gulls at that time (Arnal et al., 2014).…”
Section: Discussionmentioning
confidence: 81%
“…Despite the frequent detection of WNV in neighboring countries, no equine case of WNV has been detected in France since 2006 [7]. However, serological studies conducted from 2005–2007 in wild birds in Camargue showed that two juveniles sampled in 2006 were seropositive and that another seroconverted in 2007, thus revealing circulation of the virus in Camargue during this period [8]. In another investigation, conducted in this area during 2009, a high titer of WNV-neutralizing antibodies was found in a second year magpie ( Pica pica ), indicating its recent exposure to the virus [9].…”
Section: Introductionmentioning
confidence: 99%